KAMU KURUMLARINDA TEKNOLOJİK DÖNÜŞÜM: TÜRKİYE'DEKİ BÜYÜKŞEHİR BELEDİYELERİNİN E-BELEDİYECİLİK AÇISINDAN ANALİZİ - Öner, Kübra; Düşükcan, Muhammet (Fırat University, 2024)
Dünya küreselleşmeyle birlikte birçok alanda dönüşüm sürecine girmiştir. Bilişim teknolojilerinde küreselleşmeyle başlayan gelişmeler beraberinde bu teknolojileri kullanan kamu kurumlarını da etkilemiş; başta e-devlet kavramı ve bu kavramın yerel yönetimlere yansıması olan e-belediyecilik kavramlarının oluşmasını sağlamıştır. E-belediyecilik kavramının yerel yönetimlerden büyükşehir belediyelerine doğru uyarlanıp uyarlanmadığını, yalnızca bilgi verme ya da yerel yönetimlerin tanıtımının mı yapıldığı yoksa asıl amacına uygun olarak vatandaşın faydalanmak istediği hizmeti en doğru şekilde sunmak mı olduğunu tespit etmek maksadıyla büyükşehir belediyelerinin bu konudaki yeterlilik düzeyleri içerik analizi tekniğiyle incelenmiştir. Bu çalışmada Türkiye’de bulunan 30 büyükşehir belediyesinin web siteleri 4 ana ölçüt ve bu ölçütlere bağlı 50 alt ölçütlere göre analiz edilip büyükşehir belediyelerinin e-belediyecilik kapsamında yeterlilik düzeylerinin belirlenmesi amaçlanmaktadır. Çalışma sonunda elde edilen verilere bakıldığında e-belediyecilik konusunda büyükşehir belediyelerin son zamanlarda oluşturdukları web sitelerinin genelinin yeterli düzeyde olduğu ve eksikliklerin olduğu konularda da büyükşehir belediyelerine önerilerde bulunulmuştur.

Although climate change has been a natural phenomenon throughout human history, it has become a more serious problem today. The effects of climate change directly affect human life and the development of civilizations. Therefore, combating and adapting to climate change is the responsibility of both states and individuals. Ancient communities in Anatolia and its surroundings that lived in the past took various precautions and developed innovations against climate change. These measures and innovations can still set an example and inspire us today. To minimize the effects of climate change, risk management and measures to be taken at critical control points are vital. The aim of this study is to determine the agricultural products grown from past to present in the TRB1 region (Bingöl, Elazığ, Malatya and Tunceli) and thus contribute to the adaptation and adaptation processes to climate change. In this study, the amounts of basic products produced in the fields of crop production and livestock farming in the TRB1 region were compared according to the population of the provinces and their trends of increase or decrease were examined. Thus, the change in cultivation areas and product patterns in the TRB1 region between past and present was revealed. Today, it has been determined that the most grown products in the TRB1 region are grains. It is noteworthy that among these products, barley replaced wheat. Due to natural disasters that occur every year in the region due to climate change, large fluctuations in product quantities have occurred. The most sensitive sector in the region is beekeeping and honey production. Over time, cattle farming replaced small livestock farming in the region.
Technological Transformation in Public Institutions: Analysis of Metropolitan Municipalities in Turkiye in Terms of Municipality
Keywords: Public Sector Organisation and Management; Kamu Sektörü Organizasyonu ve Yönetimi